Bioactive peptides with multiple activities extracted from Barley (Hordeum vulgare L.) grain protein hydrolysates: Biochemical analysis and computational identification. Issue 1 (8th November 2020) - Tok, Kerem; Moulahoum, Hichem; Kocadag Kocazorbaz, Ebru; Zihnioglu, Figen
Abstract: Plant‐derived bioactive peptides demonstrate great potential given their availability and cost‐effectiveness. In this study, barley ( Hordeum vulgare L.) grain proteins were explored for bioactive peptides with potential health applications. Gross grain proteins were obtained through aqueous extraction, after which, trypsin hydrolysis was performed. The hydrolysis process provided high peptide yields reaching 11%. The peptide hydrolysates were evaluated for their antioxidant and metal chelating activities, DPP4 inhibition, deglycation, and antimicrobial activity. The obtained results demonstrated biological activity levels of great importance and comparable to reference molecules. To confirm the experimental results, barley grain protein sequences were simulated for hydrolysis and explored for potential bioactive peptides using the FeptideDB. Indeed, barley grain proteins contain a great diversity of bioactive peptides with various biological activities. The current data highlights the promising therapeutic application of barley‐derived bioactive peptides. Further molecular and sequencing approaches are necessary to identify and characterize these peptides. Practical applications: Barley ( Hordeum vulgare L.) grain proteins are widely used cereals for nutrition and beverages. Their availability and low‐cost make them good sources for functional food exploration. We have described the potential of bioactive peptides obtained from barley grain proteins that have various activities including DPP4 inhibitory, antioxidant, antimicrobial, metal chelating, and deglycation activities. This data supports the potential of these peptides in biomedicine applications as a treatment option or as food supplement. Hence, the described peptide sequences could be exploited and industrialized by artificial synthesis and be proposed as food supplements or included in protein mixes for athletes.